Childhood leukaemia: long-term excess mortality and the proportion 'cured' - Shah, A; Stiller, C; Kenward, M; Vincent, T; Eden, T; Coleman, M (Nature Publishing Group, 2008)
Survival from childhood leukaemia has increased, but the proportion of children cured is unknown. The proportion 'cured' is defined as the proportion of survivors for whom, as a group, there is no longer excess mortality compared to the general population. Average time to cure is defined as the time since diagnosis at which the excess mortality rate has declined to or below a predetermined small value. Data on children diagnosed with leukaemia during 1971-2000 in Great Britain were used to estimate trends in survival, the proportion cured and the average time to cure. Five-year survival for all types of leukaemia combined rose from 33 to 79% by 2000, time to cure increased from 12 years (95% confidence interval (CI): 11-14) to 19 years (9% CI: 14-26) for lymphoid leukaemia (average annual increase of 0.3 years; P<0.001), but remained at about 5 years for acute nonlymphoblastic leukaemia. The proportion of children cured of leukaemia has risen dramatically, but the period of excess mortality associated with lymphoid leukaemia has also increased, possibly because of late relapse, secondary malignancy and toxicity from treatment.